Relationship of Power explosive accomplishment for the team the University of Baghdad in the effectiveness of the javelin - Mutasher, Firas; Mohammed, Ahmed (Journal of Physical Education, 2015)
The purpose of research is to sweating on the relationship between the explosive power of the arm efforts and achievement with the team the University of Baghdad in the effectiveness of the javelin as well as creating a significant relationship has been mentioned a brief explanation of the power of the explosive and its definition and the factors affecting the strength researcher has used the descriptive approach to relevance nature of the problem to find where the sample of the research are Student applicants to represent the team the University of Baghdad in the effectiveness of the javelin underwent the research community of the tests used in the research, namely, (test the explosive power of arms, as well as achievement test) and then were treated statistically in order to know the relationship between research variables and moral relationship and through the results, the researcher to conclude the following: • When shooting training events and in particular the effectiveness of the javelin must pay attention to the explosive force of arms in order to achieve the farthest throw distance (achievement). Through the conclusion reached by the researcher has developed the following recommendations: • Attention to the training of physical capacity for events on which they depend mainly in the javelin distinctive characteristic explosive force it and force the maximum speed and power. • Adoption of explosive power as an indicator of physical training in basic javelin